Effects of interactions between progesterone and prostaglandin on uterine contractility in a perfused swine uterus model - Kuenzel, Julian; Geisler, Klaudija; Maltaris, Theodoros; Mueller, Andreas; Hoffmann, Inge; Schneider, Heike; Beckmann, Matthias; Dittrich, Ralf; Oppelt, Patricia (In Vivo, 2014)
Uterine quiescence at the time of embryo transfer is a prerequisite for successful in vitro fertilization (IVF). This study assessed whether prostaglandin-induced contractions in the perfused swine uterus can be reduced by progesterone.Fifty-eight non-pregnant swine uteri were perfused using an established extracorporeal perfusion model. Intrauterine pressure changes during perfusion with prostaglandin (PG) administration (PGE1, PGE2, PGF2?) and progesterone (1 pg/ml, 10 pg/ml, 25 pg/ml, 50 pg/ml) were assessed using an intrauterine double-chip microcatheter.The contraction-stimulating effect of PGs was clearly reduced by progesterone. Only PGE1 still triggered relevant contractions during continuous perfusion with progesterone solution, up to a concentration of 10 pg/ml. With PGE2 and PGF2?, a clear reduction of uterine contractility was observed even at at a progesterone concentration of 1 pg/ml.The extracorporal perfusion model of swine uteri shows that PG-induced contractions can be reduced in a dose-dependent manner by progesterone.
EVALuna2:17462